A ferrocene-based metal-organic framework material, a preparation method and application thereof
Patent Information
- Application Number
- CN202611079585.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-21
AI Technical Summary
针对水溶液中的Cr(VI)的清除和转换已经进行了较为广泛的研究,主要手段包括物理吸附、高级氧化还原、化学沉淀和膜处理等,然而这些方法主要侧重于物理富集而不是去除,难以实现彻底还原降解与无害化去除
[0013] The beneficial technical effects of this invention are as follows: The ferrocene-based metal-organic framework material exhibits high thermal and chemical stability, maintaining its integrity within a temperature range of room temperature to 300°C, and retaining its complete crystalline phase even after prolonged immersion in acidic aqueous solutions with pH = 2-6. This material constructs a donor-acceptor space charge transfer system through the synergistic interaction of the electron-rich ligand ferrocene dicarboxylic acid and the electron-deficient auxiliary ligand dipyridylphenazine, achieving efficient space charge transfer, broadening the light absorption range to approximately 800 nm, and narrowing the optical band gap to 1.96 eV. This solves the problem of low utilization efficiency in traditional photocatalysts that only respond to ultraviolet or visible light.
Smart Images

Figure CN122587228B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of MOF materials and photocatalysis, and in particular to a ferrocene-based metal-organic framework material, its preparation method, and its application. Background Technology
[0002] Chromium (Cr) is a widely used heavy metal element in industrial production, commonly used in leather processing, paint coatings, pigment preparation, electroplating, and many other industries. In industrial wastewater systems, chromium mainly exists in two forms: trivalent chromium (Cr(III)) and hexavalent chromium (Cr(VI)). Compared to the less toxic and more stable Cr(III), Cr₂O₇... 2- or CrO4 2- Due to its extremely high solubility, toxicity, and mutagenicity, Cr(VI) poses significant health risks, making the efficient removal of Cr(VI) from water bodies a key research focus in aquatic environment remediation. Extensive research has been conducted on the removal and conversion of Cr(VI) in aqueous solutions, primarily employing methods such as physical adsorption, advanced redox reactions, chemical precipitation, and membrane treatment. However, these methods mainly focus on physical enrichment rather than removal, making it difficult to achieve complete reductive degradation and harmless removal. Research has demonstrated that utilizing highly efficient photocatalysts for the harmless conversion and degradation of Cr(VI) is a feasible approach to solving the problem of chromium pollution in water bodies.
[0003] Metal-organic frameworks (MOFs) are novel porous crystalline materials formed by the coordination self-assembly of metal ions and organic ligands. With their ultra-high specific surface area, abundant pores, and designable structures, they show broad application prospects in environmental remediation, applicable to technologies such as pollutant adsorption, fluorescence sensing, and capacitive deionization. Furthermore, MOFs allow for the design, modification, and alteration of organic ligands at the molecular level, enabling precise control of their photoelectric properties and providing an ideal platform for constructing highly efficient photocatalytic materials. In particular, the introduction of electron-rich systems effectively promotes ligand-to-metal charge transfer (LMCT). Ferrocene-based composites possess excellent photoelectric properties, including customizable structures, a wide light absorption range, and a fast charge transfer rate, making them efficient and stable electron donors in many photoelectric applications. Especially noteworthy is the photoelectron transfer behavior exhibited by ferrocene upon photoexcitation, from the central iron atom to the ligand ring (MLCT). This facilitates the formation of high-energy photoelectrons and their rapid migration to the catalytic center. Therefore, ferrocene-based MOFs demonstrate promising application potential in the photocatalytic degradation of organic pollutants and the photocatalytic reduction of heavy metal ions in water bodies. Summary of the Invention
[0004] To address the aforementioned technical analysis and existing problems, this invention provides a ferrocene-based metal-organic framework material, its preparation method, and its applications. The ferrocene-based metal-organic framework material exhibits high thermal stability and excellent photocatalytic performance, demonstrating good Cr(VI) removal efficiency in both simulated water and under a xenon lamp. It shows promising application potential in the photocatalytic degradation of organic pollutants and the photocatalytic reduction of heavy metal ions in water.
[0005] This invention is achieved through the following technical solution: A ferrocene-based metal-organic framework material with the general chemical formula CdFeC 30 H 18 N4O4, named DZU-403, has ferrocene dicarboxylic acid (H2FcDC) as the main ligand (CAS number: 1293-87-4) and dipyridophenezine (dppz) as the auxiliary ligand (CAS number: 19535-47-8).
[0006] Furthermore, DZU-403 crystallizes in the monoclinic system in space group P2 / c, with the following cell parameters: a =8.770(2)Å, b =14.847(4)Å, c =19.154(5)Å; α =90°, β =96.837(5)°, γ =90°.
[0007] Furthermore, the asymmetric structural unit of DZU-403 contains one Cd. 2+ The center, one dppz ligand, and one deprotonated FcDC 2- Ligand, Cd 2+ With two nitrogen atoms from the dppz ligand and from FcDC 2- The four carboxylic acid oxygen atoms of the ligand coordinate to form a distorted octahedral geometry; Two adjacent Cd 2+ Ions via FcDC 2- The carboxylic acid groups of the ligands are linked to form a binuclear Cd2(COO)2 cluster, and then each FcDC 2- The ligand connects two metal clusters to form a one-dimensional chain structure; the dppz ligand binds to Cd through the pyridine nitrogen atom. 2+ The chelation and coordination of ions result in parallel alignment on the same side of the one-dimensional chain. Finally, a three-dimensional supramolecular network structure is constructed through intermolecular interactions between adjacent chains.
[0008] FcDC on a chain 2-The dppz ligands on the unit and adjacent chains are vertically aligned, and the ferrocene Cp ring is almost orthogonal to the dppz plane. The iron center is 4.2 Å away from the dppz plane, and the nearest carbon atoms in the Cp ring are 3.3 Å and 3.5 Å away from the dppz plane. This configuration, which enables partial orbital overlap, facilitates efficient electronic communication between the electron-rich ironene donor and the electron-deficient dppz acceptor, establishing a well-defined TSCT pathway within the framework.
[0009] The present invention also provides a method for preparing the ferrocene-based metal-organic framework material, comprising the following steps: S1. Add the organic ligands H2FcDC, dppz and cadmium nitrate tetrahydrate to a mixed solvent of DMF, methanol and deionized water and mix thoroughly. S2. The mixture is sealed and subjected to ultrasonic treatment to carry out a solvothermal reaction; after cooling and centrifugation, dark brown crystals are obtained. The crystals are washed with ethanol and then vacuum dried to obtain ferrocene-based metal-organic framework materials.
[0010] Furthermore, the mass ratio of H2FcDC, dppz, and Cd(NO3)2·4H2O is 7:7:15; the volume ratio of DMF, methanol, and deionized water in the mixed solvent is 1:1:1; and the ratio of the total volume of the mixed solvent to the total mass of the ligand is 1.35 mL:14 mg.
[0011] Furthermore, the solvothermal reaction is performed under oven heating at 90-100°C for 36-48 hours.
[0012] This invention also provides the application of the ferrocene-based metal-organic framework material in the photocatalytic reduction of dichromate ions Cr(VI) to Cr(III) under visible light irradiation.
[0013] The beneficial technical effects of this invention are as follows: The ferrocene-based metal-organic framework material exhibits high thermal and chemical stability, maintaining its integrity within a temperature range of room temperature to 300°C, and retaining its complete crystalline phase even after prolonged immersion in acidic aqueous solutions with pH = 2-6. This material constructs a donor-acceptor space charge transfer system through the synergistic interaction of the electron-rich ligand ferrocene dicarboxylic acid and the electron-deficient auxiliary ligand dipyridylphenazine, achieving efficient space charge transfer, broadening the light absorption range to approximately 800 nm, and narrowing the optical band gap to 1.96 eV. This solves the problem of low utilization efficiency in traditional photocatalysts that only respond to ultraviolet or visible light.
[0014] Under visible light irradiation, this material can efficiently photocatalytically reduce the highly toxic dichromate ion Cr(VI) to the less toxic Cr(III). Furthermore, its catalytic efficiency is significantly enhanced when synergistically combined with small-molecule organic acids (such as tartaric acid), achieving a near 100% removal rate of 50 mg / L Cr(VI) within 70 minutes. This material exhibits highly efficient photocatalytic reduction of Cr(VI) and good recyclability; its photocatalytic activity shows no significant decay after three cycles. Its powder X-ray diffraction pattern closely matches the simulated pattern, demonstrating excellent stability and reusability. In addition, this material generates a rapid and repeatable photocurrent response under visible light irradiation, with low charge transfer resistance, which is beneficial for the separation and migration of photogenerated carriers. Attached Figure Description
[0015] Figure 1 Cd in ferrocene-based metal-organic frameworks 2+ Coordination environment diagram of the center; Figure 2 It is the FcDC in ferrocene-based metal-organic framework materials 2- Coordination pattern diagram of ligands; Figure 3 This is a one-dimensional chain structure diagram of a ferrocene-based metal-organic framework material; Figure 4 This is a three-dimensional supramolecular network diagram of ferrocene-based metal-organic framework materials; Figure 5 This is a schematic diagram showing the distance, overlap, and filling pattern between donor ligands and acceptor ligands in ferrocene-based metal-organic framework materials. Figure 6 This is an X-ray powder diffraction pattern of a ferrocene-based metal-organic framework material; Figure 7 This is a thermogravimetric analysis diagram of ferrocene-based metal-organic framework materials; Figure 8 The ultraviolet-visible absorption spectra of ferrocene-based metal-organic framework materials and their ligands; Figure 9 This is a bandgap diagram of ferrocene-based metal-organic framework materials and their ligands; Figure 10 This is the Mott-Schottky diagram of ferrocene-based metal-organic frameworks; Figure 11 This is a band structure comparison diagram of ferrocene-based metal-organic framework materials; Figure 12 This is a transient photocurrent response diagram of a ferrocene-based metal-organic framework material; Figure 13 This is the electrochemical impedance spectroscopy of a ferrocene-based metal-organic framework material; Figure 14This is a graph showing the photocatalytic performance of different catalyst systems for reducing Cr(VI) (pH=2) using ferrocene-based metal-organic frameworks; Figure 15 This is a graph showing the rate constants (K values) of the reduction performance of different catalyst systems for ferrocene-based metal-organic framework materials; Figure 16 The graph shows the dark adsorption and photocatalytic reduction performance of Cr(VI) of ferrocene-based metal-organic framework materials under different TA dosages and pH values. Figure 17 This is an X-ray photoelectron spectrum of a ferrocene-based metal-organic framework material; Figure 18 This is a graph showing the photocatalytic cycling performance of ferrocene-based metal-organic framework materials; Figure 19 The figure shows the quenching results of Cr(VI) reduction in ferrocene-based metal-organic framework materials. Figure 20 This is the electron spin resonance spectrum of a ferrocene-based metal-organic framework material. Detailed Implementation
[0016] Example 1
[0017] Cd(NO3)2·4H2O (75 mg), H2FcDC (35 mg), and dppz (35 mg) were placed in a 10 mL vial, followed by the addition of N,N-dimethylformamide (DMF) (2.25 mL), methanol (2.25 mL), and deionized water (2.25 mL). The mixture was sealed and sonicated for 10 min until no precipitate was observed, then heated in a 90°C oven for 48 h. Subsequently, dark brown crystals of DZU-403 were obtained by centrifugation, activated with EtOH, washed, and vacuum dried, with a yield of approximately 61%.
[0018] Example 2
[0019] Cd(NO3)2·4H2O (75 mg), H2FcDC (35 mg), and dppz (35 mg) were placed in a 10 mL vial, followed by the addition of DMF (2.25 mL), methanol (2.25 mL), and deionized water (2.25 mL). The mixture was sealed and sonicated for 10 min until no precipitate was observed, then heated in a 100°C oven for 36 h. Subsequently, dark brown crystals of DZU-403 were obtained by centrifugation, activated with EtOH, washed, and vacuum dried, with a yield of approximately 57%.
[0020] The ferrocene-based metal-organic framework materials prepared in Examples 1 and 2 are identical and are characterized as follows: (1) Determination of crystal structure Suitable crystals were selected under a microscope, mounted on glass fibers, and diffraction data were collected using a Bruker APEXII single-crystal diffractometer at different temperatures (193 K, 298 K) and with different targets (copper-palladium, molybdenum). The diffractometer used Ka-rays monochromated with a graphite monochromator to collect data in a φ-ω manner. During data reconstruction, empirical absorption and correction were performed using the SADABS program. The structure was solved using a direct method, and optimization based on the F2 full-matrix least squares method was performed using the SHELXTL software package. To further refine the crystal data, the OLEX2 software was used. In the final round of refinement, anisotropic refinement was performed on non-hydrogen atoms, ensuring that all non-hydrogen atoms were anisotropically refined. The contribution of disordered solvent molecules was handled using the SQUEEZE program implemented in PLATON. The crystallographic data are shown in Table 1.
[0021] Table 1 Crystal data and structural refinement parameters of ferrocene-based metal-organic frameworks
[0022] (2) Powder diffraction characterization of phase purity To examine the phase purity, crystallinity, and structural stability of the samples, X-ray powder diffraction tests were performed on newly synthesized samples and samples that had been soaked in a series of acidic aqueous solutions (pH = 2-6) in the range of 5-50°.
[0023] The single-crystal structure powder diffraction pattern simulation conversion was performed using Mercury 1.4.2.
[0024] Figure 1-4 The diagram shows the structure of a ferrocene-based metal-organic framework. It can be seen that the asymmetric structural unit of DZU-403 contains one Cd atom. 2+ The center, one dppz ligand, and one deprotonated FcDC 2- The ligands, Cd1 with two nitrogen atoms from the dppz ligands and from FcDC, 2- The four carboxylic acid oxygen atoms of the ligand coordinate to form a distorted octahedral geometry; Two adjacent Cd 2+ Ions via FcDC 2- The carboxylic acid groups of the ligands are linked to form a binuclear Cd2(COO)2 cluster, and then each FcDC 2- The ligand connects two metal clusters to form a one-dimensional chain structure; the dppz ligand binds to Cd through the pyridine nitrogen atom. 2+ The chelation and coordination of ions result in parallel alignment on the same side of the one-dimensional chain. Finally, a three-dimensional supramolecular network structure is constructed through intermolecular interactions between adjacent chains.
[0025] See Figure 5 FcDC on a chain2- The dppz ligands on the unit and adjacent chains are vertically aligned, and the ferrocene Cp ring is almost orthogonal to the dppz plane. The iron center is 4.2 Å away from the dppz plane, and the nearest carbon atoms in the Cp ring are 3.3 Å and 3.5 Å away from the dppz plane. This configuration, which enables partial orbital overlap, facilitates efficient electronic communication between the electron-rich ironene donor and the electron-deficient dppz acceptor, establishing a well-defined TSCT pathway within the framework.
[0026] Figure 6 This is the powder diffraction pattern of the ferrocene-based metal-organic framework material. The figure shows that the experimental PXRD pattern of the synthesized sample is in high agreement with the simulated pattern based on single-crystal data, indicating good phase purity of DZU-403. The sharp diffraction peaks further demonstrate its high crystallinity. Notably, the diffraction peaks of the sample after immersion in a series of acidic aqueous solutions (pH=2-6) remain highly consistent with those of the synthesized sample, indicating excellent structural stability of DZU-403 in acidic environments.
[0027] (3) Thermal stability Figure 7 The thermogravimetric analysis (TGA) curve of the ferrocene-based metal-organic framework material shows that its mass remains relatively constant between room temperature and 300°C, indicating good thermal stability within this temperature range. When the temperature rises to 350°C, the sample mass begins to gradually decrease. A rapid initial weight loss of approximately 14% occurs between 350°C and 400°C, attributed to the thermal decomposition of organic ligands and the breaking of coordination bonds. A further weight loss of approximately 12% occurs between 400°C and 500°C, representing further disintegration of the material's framework structure. Weight loss plateaus between 500°C and 600°C, suggesting the formation of transitional intermediate structures within the system. Above 600°C, the sample mass decreases again, with a residual weight of approximately 40% at 800°C, primarily consisting of inorganic residues such as metal oxides. Overall, the thermal decomposition initiation temperature of DZU-403 is approximately 350°C, which meets the basic requirements for thermal stability in conventional photocatalytic reactions.
[0028] (4) Analysis of space charge transfer effect Figure 8 The figures show the UV-Vis absorption spectra of this ferrocene-based metal-organic framework material and its ligands. The figures indicate that, compared to its individual building blocks dppz and FcDC... 2- The ligand, DZU-403, exhibits a significantly broader and stronger absorption band. The absorption extends to approximately 800 nm, covering most of the visible light spectrum. This remarkable spectral broadening confirms a strong space charge transfer (TSCT) interaction between the electron donor and electron acceptor dppz units.
[0029] Figure 9This is a bandgap plot for the ferrocene-based metal-organic framework material and its ligands. The plot shows that DZU-403 has a direct bandgap of 1.96 eV, compared to dppz (2.87 eV) and FcDC. 2- The (2.09 eV) ligand exhibits a significantly reduced bandgap, and this reduction in required excitation energy is highly beneficial for the generation of photogenerated carriers. Extended absorption, narrowed bandgap, and computational analysis indicate that DA integration in DZU-403 effectively promotes photon utilization and creates a favorable charge-separated electronic structure upon photoexcitation, which is crucial for enhancing photocatalytic activity.
[0030] (5) Band structure and charge carrier dynamics Figure 10 The figure shows the Mott-Schottky plots of this ferrocene-based metal-organic framework material. The positive slopes of the Mott-Schottky measurements of DZU-403 at 500, 1000, and 1500 Hz confirm its n-type semiconductor characteristics. The flat-band potential (Efb) at the intersection of the extrapolated lines is -0.56 V for Ag / AgCl.
[0031] Figure 11 This is a band structure diagram of the ferrocene-based metal-organic framework material. The diagram shows that the minimum conduction band (CB) potential is estimated to be approximately -0.32 eV, while the maximum valence band (VB) potential relative to NHE, calculated based on the band gap, is +1.64 eV. The material's conduction band potential (-0.32 eV) is significantly negative than the Cr(VI) / Cr(III) reduction potential (approximately +1.05 eV relative to NHE, pH=2). The conduction band photogenerated electrons possess sufficient reduction potential, thermodynamically fully satisfying the requirements for the photoreduction of Cr(VI) to Cr(III), exhibiting a very strong reduction driving force. Theoretically, this could achieve the photocatalytic reduction of hexavalent chromium.
[0032] Figure 12 The transient photocurrent response of this ferrocene-based metal-organic framework material is shown. The figure indicates that DZU-403 exhibits a rapid and repeatable anodic photocurrent under intermittent visible light irradiation. After illumination, the photocurrent rapidly increases to approximately 2.25 μA cm⁻¹. -2 The maximum value of the photocurrent stabilized at a steady-state density of approximately 1.7 μA after multiple switching cycles. This stable photocurrent response indicates the efficient generation and continuous separation of photogenerated electron-hole pairs, which can be repeatedly used for photocatalytic reduction of Cr(VI).
[0033] Figure 13The image shows the electrochemical impedance spectroscopy (EIS) of this ferrocene-based metal-organic framework material. The spectrum exhibits a semi-circular appearance in the high-frequency region, with an estimated charge transfer resistance (Rct) of approximately 160 Ω. This resistance is significantly lower than that of conventional MOF-based photocatalysts, indicating efficient charge transfer to the electrolyte interface and promoting surface redox reactions. In the low-frequency region, a Warburg-type tail is observed, suggesting a diffusion-controlled process.
[0034] (6) Photocatalytic performance Figure 14 This figure shows the photocatalytic performance of the ferrocene-based metal-organic framework material in reducing Cr(VI) (pH=2) using different catalyst systems. The figure indicates that without a catalyst, the DZU-403 system exhibits almost no adsorption of Cr(VI). However, when oxalic acid (OA), citric acid (CA), and tartaric acid (TA) are introduced, the material shows some adsorption of Cr(VI), reducing the Cr(VI) concentration to approximately 80% of its initial value. Under visible light irradiation, all DZU-403 / acid systems exhibit significant photocatalytic reduction activity. Among the three acids, TA proved to be the most effective pore scavenger. In the DZU-403 / TA system, the Cr(VI) concentration decreased rapidly within the first 10 minutes, reaching almost 100% removal after 70 minutes. In contrast, the DZU-403 / CA and DZU-403 / OA systems achieved removal rates of approximately 80% and 40%, respectively, after 90 minutes. The results of the blank control experiment showed that when only organic acid was added or when only visible light was irradiated without catalyst, the Cr(VI) content in the system did not decrease significantly, proving that the synergistic presence of DZU-403 catalyst and small molecule organic acid is a necessary condition for achieving efficient photoreduction of Cr(VI).
[0035] Figure 15 This is a graph showing the reduction performance (K-values) of different systems of this ferrocene-based metal-organic framework material. The graph indicates that the reaction rate constant (k) of the DZU-403 / TA system can reach 0.06245 min. -1 This value is approximately equal to that of the DZU-403 single system (0.00344 min). -1 It was 18 times higher than that of the pure TA system (0.00145 min), and significantly higher than that of the pure TA system (0.00145 min). -1 ) or under light-only conditions (0.00225 min) -1 The above kinetic data confirm that DZU-403 and TA have a synergistic effect, effectively achieving the reduction and removal of Cr(VI).
[0036] Figure 16The figure shows the performance of the ferrocene-based metal-organic framework material TA system under different conditions. The figure indicates that the Cr(VI) reduction and removal efficiency gradually increases with decreasing pH, with the optimal catalytic performance observed at pH=2. Simultaneously, increasing the tartaric acid dosage significantly accelerates the reduction reaction rate. When the TA dosage increases from 50 μL to 150 μL, the catalytic effect is significantly enhanced, and Cr(VI) can be almost completely removed within 10 minutes under 150 μL TA conditions.
[0037] Figure 17 This is the X-ray photoelectron spectrum of the ferrocene-based metal-organic framework material. The figure shows that the characteristic peaks with binding energies of 577.35 eV and 586.58 eV correspond to the Cr 2p group of Cr(III), respectively. 3 / 2 and Cr 2p 1 / 2 No peaks characteristic of Cr(VI) were observed in the spectrum, confirming that the photoreduction process completely converted toxic Cr(VI) into less toxic Cr(III). The reusability and structural stability of DZU-403 were evaluated by three consecutive photocatalytic cycles; the catalyst maintained high activity without significant loss after three cycles. Figure 18 Furthermore, the powder X-ray diffraction (PXRD) of the recovered catalyst still maintained good diffraction peaks, confirming the excellent structural stability of DZU-403 under the reaction conditions.
[0038] (7) Mechanism research Figure 19 This is a graph showing the effect of adding a photoelectron trapping agent on the catalytic performance of the ferrocene-based metal-organic framework material. The graph shows that adding KBrO3 to the system to trap photoelectrons inhibited the reduction efficiency by 18% after 60 min, directly indicating the effect of photogenerated electrons (electrons). - ) is the main reducing agent.
[0039] Figure 20 This is the electron spin resonance (EPR) spectrum of the ferrocene-based metal-organic framework material. The figure shows that when tested using 2,2,6,6-tetramethylpiperidine oxygen radical (TEMPO) as a spin trapper, a characteristic triplet signal of TEMPO was observed under dark conditions. After irradiation with visible light for 2 minutes, the signal intensity decreased, and after 5 minutes, the signal weakened significantly. This decrease in the EPR signal is attributed to the reduction of photoelectron pairing with TEMPO, directly demonstrating the electron-electron resonance (EPR) process during photocatalysis. - The generation Based on the above experimental evidence, a reasonable photocatalytic mechanism for the reduction of Cr(VI) by DZU-403 is proposed. Under visible light irradiation, the ferrocene donor units in DZU-403 absorb light and generate electron-hole pairs. The close spatial arrangement between the ferrocene donor and the dppz acceptor promotes efficient TSCT and facilitates the separation of photogenerated carriers. The voids are rapidly consumed by tartaric acid (TA), which acts as a sacrificial agent and is oxidized to carbon dioxide and water, thereby inhibiting charge recombination. Simultaneously, photogenerated electrons migrate to the catalyst surface, carrying adsorbed Cr2O7. 2- Ions reduced to Cr 3+ The overall redox process can be described by the following equation: DZU-403 + hv → DZU-403 (e - + h + (1) Cr2O7 2- + 14H + + 6e - → 2Cr 3+ + 7H2O (2) TA + h + → CO2+ H2O + other products (3).
Claims
1. A ferrocene-based metal-organic framework material, characterized in that: The general chemical formula is CdFeC 30 H 18 N4O4, with ferrocene dicarboxylic acid H2FcDC as the main ligand and dipyridinidine dppz as the auxiliary ligand.
2. The ferrocene-based metal-organic framework material according to claim 1, characterized in that: The ferrocene-based metal-organic framework material is crystallized in the P2 / c space group of the monoclinic crystal system, with the following cell parameters: a=8.770(2)Å, b=14.847(4)Å, c=19.154(5)Å; α=90°, β=96.837(5)°, γ=90°.
3. The ferrocene-based metal-organic framework material according to claim 1, characterized in that: The asymmetric structural unit of the ferrocene-based metal-organic framework material contains one Cd. 2+ The center, one dppz ligand, and one deprotonated FcDC 2- Ligand, Cd 2+ With two nitrogen atoms from the dppz ligand and from FcDC 2- The four carboxylic acid oxygen atoms of the ligand coordinate to form a distorted octahedral geometry; Two adjacent Cd 2+ Ions via FcDC 2- The carboxylic acid groups of the ligands are linked to form a binuclear Cd2(COO)2 cluster, each FcDC 2- The ligand connects two Cd2(COO)2 clusters to form a one-dimensional chain structure; the dppz ligand binds to Cd through the pyridine nitrogen atom. 2+ The chelation coordination of ions results in parallel arrangement on the same side of the one-dimensional chain; adjacent one-dimensional chains construct a three-dimensional supramolecular network structure through intermolecular interactions.
4. A method for preparing a ferrocene-based metal-organic framework material as described in any one of claims 1-3, characterized in that: Includes the following steps: S1. Add the organic ligands H2FcDC, dppz and Cd(NO3)2·4H2O to a mixed solvent of DMF, methanol and deionized water and mix thoroughly. S2. The mixture is sealed and subjected to ultrasonic treatment to carry out a solvothermal reaction; after cooling and centrifugation, dark brown crystals are obtained. The crystals are washed with ethanol and then vacuum dried to obtain ferrocene-based metal-organic framework materials.
5. The method for preparing the ferrocene-based metal-organic framework material according to claim 4, characterized in that: The mass ratio of H2FcDC, dppz, and Cd(NO3)2·4H2O is 7:7:15; the volume ratio of DMF, methanol, and deionized water in the mixed solvent is 1:1:1; and the ratio of the total volume of the mixed solvent to the total mass of the ligand is 1.35 mL:14 mg.
6. The method for preparing the ferrocene-based metal-organic framework material according to claim 5, characterized in that: The solvothermal reaction is performed by heating in an oven at 90-100°C for 36-48 hours.
7. The application of a ferrocene-based metal-organic framework material as described in any one of claims 1-3 in the photocatalytic reduction of hexavalent chromium to trivalent chromium under visible light irradiation, characterized in that: The ferrocene-based metal-organic framework material works synergistically with small molecule organic acids to catalytically reduce hexavalent chromium under visible light irradiation.
8. The application of the ferrocene-based metal-organic framework material according to claim 7 in the photocatalytic reduction of hexavalent chromium to trivalent chromium under visible light irradiation, characterized in that: The small molecule organic acid is selected from one of oxalic acid, citric acid, and tartaric acid.
9. The application of the ferrocene-based metal-organic framework material according to claim 8 in the photocatalytic reduction of hexavalent chromium to trivalent chromium under visible light irradiation, characterized in that: The small molecule organic acid is tartaric acid.
Citation Information
Patent Citations
Copper sulfide cluster catalytic material with core-shell structure as well as preparation method and application of copper sulfide cluster catalytic material
CN118384923A
Non-platinum group metal electrocatalysts using metal organic framework materials and method of preparation
US20120077667A1